2024
DOI: 10.1200/po.23.00439
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Baseline Tumor-Specific Neoantigens and CD8+ T-Cell Infiltration With Immune-Related Adverse Events Secondary to Immune Checkpoint Inhibitors

Csaba Kerepesi,
Hassan Mohammed Abushukair,
Biagio Ricciuti
et al.

Abstract: PURPOSE Recent evidence has shown that higher tumor mutational burden strongly correlates with an increased risk of immune-related adverse events (irAEs). By using an integrated multiomics approach, we further studied the association between relevant tumor immune microenvironment (TIME) features and irAEs. METHODS Leveraging the US Food and Drug Administration Adverse Event Reporting System, we extracted cases of suspected irAEs to calculate the reporting odds ratios (RORs) of irAEs for cancers treated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The close association between tumor immunogenicity (mutational burden, baseline tumor-specific neoantigens, and CD8 T-cell Infiltration) and irAE during ICI therapies has been reported by several authors (13,14). Originally conceived to selectively stimulate anti-tumor T cells (15), anti-CTLA-4 monoclonal antibodies have been shown to induce pan-T cell activation in clinical settings, compromising the host's immune tolerance to healthy self-tissues.…”
Section: Discussionmentioning
confidence: 91%
“…The close association between tumor immunogenicity (mutational burden, baseline tumor-specific neoantigens, and CD8 T-cell Infiltration) and irAE during ICI therapies has been reported by several authors (13,14). Originally conceived to selectively stimulate anti-tumor T cells (15), anti-CTLA-4 monoclonal antibodies have been shown to induce pan-T cell activation in clinical settings, compromising the host's immune tolerance to healthy self-tissues.…”
Section: Discussionmentioning
confidence: 91%
“…To address these challenges, a recent modeling study, based on multiomics investigations, found a close correlation between the number of InDel and point mutations of cancer cells, the amount of tumor-infiltrating lymphocytes, and the risk of immune-related adverse events, highlighting the importance of mutational evaluations of neoplasms before indicating combinatorial immune checkpoint therapies. This modeling also suggests that upon the elevated predicted risk of immune-related adverse events, a reduction in the dosage of immune checkpoint inhibitors circumvents the unfolding of their severe side effects [ 169 ].…”
Section: Tumor-agnostic Treatment Philosophy In Current Clinical Onco...mentioning
confidence: 99%